2005
DOI: 10.1002/j.2161-4296.2005.tb01727.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Satellite-Based Augmentation System Grid Size at Low Latitudes in the Indian Zone

Abstract: The Total Electron Content (TEC) measured from a station situated near the northern crest of the equatorial anomaly is compared with that obtained from models such as the Parameterized Ionospheric Model (PIM 1.6) and International Reference Ionosphere (IRI-95) for well over one solar cycle (1977 -1990). The limitations of conversion from vertical to slant TEC and vice versa as required for GPS ionospheric corrections in the equatorial region are discussed. It is found that the correspondence among the vertical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…To avoid the multipath effect an elevation cut-off of 20 • is selected. For GPS TEC data an elevation cut-off of 50 • is considered to make the slant to vertical conversion more accurate (Paul et al, 2005). Appropriate satellite and receiver bias corrections are incorporated.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…To avoid the multipath effect an elevation cut-off of 20 • is selected. For GPS TEC data an elevation cut-off of 50 • is considered to make the slant to vertical conversion more accurate (Paul et al, 2005). Appropriate satellite and receiver bias corrections are incorporated.…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…Different models such as IRI, PIM, SLIM and SUPIM are available for evaluation of TEC. But studies (Ezquer et al, 2004;Paul et al, 2005) reveal that no model in general is sufficient to represent TEC variation around the anomaly crest region. Development of a model requires several steps to be followed.…”
Section: Introductionmentioning
confidence: 99%
“…During 1999–2002, combined GPS‐GLONASS receivers were operated at some locations in India where it was reported that availability of GLONASS satellites was limited from equatorial locations (Banerjee et al, ). Studies conducted earlier have reported that the detrimental effects of the sharp latitudinal gradients of ionization occurring in the equatorial region may be limited if sufficient number of satellite links are available at high elevation angles in excess of 60° (Paul et al, ). It has been observed using total electron content (TEC) measured in 2004 along a chain of stations located more or less along 77°E meridian under the Indian Satellite‐Based Augmentation System (SBAS) program GPS‐aided Geo Augmented Navigation (GAGAN) that the median grid scale of latitude and longitude for total electron content variation less than 3 TECU (for an acceptable range error of 50 cm) varied from (0.64°–0.87°) × (0.23°–0.49°) at elevation angles greater than 70° (Paul, Das, et al, ).…”
Section: Introductionmentioning
confidence: 99%